Study of the Difference in Biodegradation Rate of LAS (Linear Alkylbenzene Sulfonates) and MES (Methyl Ester Sulfonate) Surfactants by Pseudomonas putida and Bacillus megaterium - Dzurrahmi, Baiq Dini Najia; Sedijani, Prapti; Muhlis, Muhlis (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Linear Alkylbenzene Sulfonate (LAS) is the most widely used surfactant in industrial detergent formulations, generating waste that poses potential risks to environmental quality and human health. As an environmentally friendly alternative, palm oil–based Methyl Ester Sulfonate (MES) has renewable and biodegradable properties, stability in hard water and high salinity, and a faster degradation rate than LAS. However, direct comparative studies on the biodegradation rates of LAS and MES are still limited. Therefore, this study aimed to compare the biodegradation ability of Pseudomonas putida and Bacillus megaterium toward LAS and MES in vitro using the MBAS method. The experiment employed a Completely Randomized Design with a two-factor factorial arrangement and three replications, resulting in 12 experimental units. Biodegradation rates were determined by measuring surfactant concentrations at days 0, 2, 4, 6, and 8 using UV-Vis spectrophotometry and linear regression analysis. The results showed a decrease in surfactant concentration over time in all treatments. Statistical analysis indicated no significant difference between LAS and MES biodegradation rates, but significant differences between bacterial species and their interaction with surfactant type.